The Role of Islamic Microfinance Institutions in Supporting MSME Digital Transformation in Indonesia - Lili Puspita Sari; Desmadi Saharuddin; Muhammad Said (Iqtishodia: Jurnal Ekonomi Syariah, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy by contributing significantly to employment and national economic growth. However, many MSMEs still face structural challenges, particularly limited access to financing and low digital readiness. In the era of digital economy expansion, Islamic microfinance institutions have the potential to support MSME digital transformation through inclusive and Sharia-compliant financial services. This study aims to analyze the role of Islamic microfinance institutions in supporting the digitalization of MSMEs in Indonesia.  This research employs a descriptive qualitative approach using a literature review method. Data were collected from academic journals, government reports, and policy documents sourced from databases such as Google Scholar and national journal repositories. The selected literature was analyzed using content analysis through data reduction, categorization, and thematic interpretation. The findings show that Islamic microfinance institutions contribute to MSME digitalization by expanding access to Sharia-compliant financing, providing business mentoring, and improving managerial and digital capacities of MSME actors. However, challenges remain, including limited capital, low digital literacy, and technological constraints. Islamic microfinance institutions play a strategic role in supporting inclusive and sustainable MSME digitalization in Indonesia.